Livestock Feeds Assessment in Southern Highlands in Tanzania - Mwendia, Solomon W.; Mwilawa, Angello; Nzogela, Beatus; Kizima, Jonas; Mangesho, Walter E.; Loina, Rose; Bwire, Julius M.N.; Notenbaert, An Maria Omer (Tropentag, 2019)
Importance of livestock in smallholder farms in Africa continue to be significant in households’ nutrition, incomes and for socio-cultural reasons. However, the sector faces various challenges including management, diseases and feeding among others. With the estimated doubling of demand for animal source foods especially in sub-Saharan Africa, due to rise in human population, efforts for improving livestock productivity are needed. Amongst the costs involved in cattle production, the feeding component takes 70% suggesting greater attention is required in feeding interventions for success to be realised. In an effort to contribute to improvement of livestock production in Southern Tanzania highlands, current feeding status was assessed in 3 districts (Mufindi, Njombe, Rugwe) following Feeds Assessment Tool protocol (FEAST https://www.ilri.org/feast). Information captured entailed; land size categories, livestock species reared, feed resources and seasonality, contribution of livestock to household incomes and most suited interventions were elucidated. In the three districts, dairy remains most prevalent amongst livestock species kept, and livestock in general is important for household incomes. Analysis suggest interventions on feeds and forages addressing protein and energy supply would be crucial, including forages suitable under cut and carry context, prevalent under smallholder farmers settings. Dry seasons are Characterized by inadequate feed resources. The information will guide selection of forage options to be tested through farmer participation, under Climate Smart Dairy Project (2019-2021) in the three districts. Identified farmer acceptable and productive forages will be recommended for the areas other similar ecologies, and by extension support forage development in Tanzania.